PENGARUH CITRA MEREK DAN MEREK PERUSAHAAN TERHADAP PILIHAN KONSUMEN YANG DIMEDIASI EKUITAS MEREK (STUDI PADA MEREK PASTA GIGI PEPSODENT) - Rudi Permana Ginting; Permana Honneyta Lubis (Jurnal Manajemen Inovasi, 2020)
The aim of this study is to investigate the effect of Brand Image and Corporate Branding on Costumer Choice with Brand Equity as Mediating variable. The present study was conducted on 100 costumer of Pepsodent in Banda Aceh.  The sampling using probability sampling method. This study uses three variables, namely the independent variable, dependent variable, and mediating variable. HLM is used as a method of analysis to determine the effect of variables which involved in this research. Questionnaires measured using a Likert’s Scale. Test validity, reliability, normality, and analysis regression using SPSS Statistics 20. The findings indicate that Brand Image and Corporate Branding has positive influence on Brand Equity and Costumer Choice; Brand Equity mediate the relationship between Brand Image  and Corporate Branding on Costumer Choice.